The Gingival Oral Lichen Planus: A Periodontal-Oral Medicine Approach - Abdulhameed Alsarraf; Kunj Mehta; Nabil Khzam (Case Reports in Dentistry)
We present a case of a 77-year-old female who suffered from oral lichen planus (OLP) involving her gingiva and bilateral buccal mucosa for over 6 months. We showed that oral hygiene measures and conventional periodontal treatment and strict maintenance were sufficient to control the gingival involvement of OLP. The mechanism of OLP is complex and not yet fully understood. The focus of discussion in our case was that knowledge and understanding of gingival pathology are fundamental for a determined management approach. Our case was managed according to the suggested protocols in previous case studies. A multidisciplinary approach allowed for accurate diagnosis and treatment tailored to the presented case.